Tinjauan Yuridis terhadap Putusan Niet Ontvankelijke Verklaard dalam Perkara Gugatan Kurang Pihak - Dara Sari Sinaga; Akmaluddin Syahputra (Unissula, 2023)
Lawsuit is a letter submitted by the plaintiff against the defendant to the District Court which contains a claim for rights which contains a dispute and forms the basis for examining a case and proving the truth of a right. This legal research aims to find out and analyze civil cases that were sued through the District Court, how to fulfill the requirements in making a lawsuit so that it was not rejected by the Panel of Judges and the reasons that resulted in a lawsuit from the plaintiff in the case decision case Number. 361/Pdt.G/2017/PN JKT PST Niet Ontvankelijke Verklaard. The method used in this research is normative juridical research where the author collects data in the form of basic legal materials and additional legal materials. In this journal research, it can be concluded that a lawsuit submitted to the Court must meet the formal requirements as stipulated in Article 118 HIR, the plaintiff must also be more careful and careful in making a claim based on existing legal facts so that it can produce a positive judge's decision with a sense of justice for each party to the litigation.Â